Thúy Ngân
25 tháng 8 2017 lúc 10:23

\(\frac{2011.2010-1}{2009.2011+2010}=\frac{2011.\left(2009+1\right)-1}{2009.2011+2010}\)

\(=\frac{2011.2009+2011-1}{2009.2011+2010}\)

\(=\frac{2011.2009+2010}{2009.2011+2010}\)

\(=1\)

Nhớ k vs kp với mik nhé,mấy man!

Bình luận (0)
Nguyễn Thiện Nhân
28 tháng 7 2018 lúc 21:49

đổi k ko

Bình luận (0)
Bánh sữa Suga
19 tháng 3 2020 lúc 9:00

2011×2010-1

2009×2011+2010

Bình luận (0)
Bánh sữa Suga
19 tháng 3 2020 lúc 9:01

Bài trên =1

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN